Isolation of chromatin from dysfunctional telomeres reveals an important role for Ring1b in NHEJ-mediated chromosome fusions - Bartocci, Cristina (2014)
When telomeres become critically short DNA damage response factors are recruited at chromosome ends initiating a cellular response to DNA damage. We performed Proteomic Isolation of Chromatin fragments (PICh) to define changes in chromatin composition that occur upon onset of acute telomere dysfunction triggered by depletion of the telomere-associated factor TRF2. This unbiased purification of telomere-associated proteins in functional or dysfunctional conditions revealed the dynamic changes in chromatin composition that take place at telomeres upon DNA damage induction. Based on our results, we describe a critical role for the polycomb group protein Ring1b in NHEJ-mediated end-to-end chromosome fusions. We show that cells with reduced levels of Ring1b have a reduced ability to repair uncapped telomeric chromatin. Our data represent the first unbiased isolation of chromatin undergoing DNA damage and are a valuable resource to map the changes in chromatin composition in response to DNA damage activation.